2018
DOI: 10.1111/jeb.13224
|View full text |Cite
|
Sign up to set email alerts
|

Linking genotype to phenotype in a changing ocean: inferring the genomic architecture of a blue mussel stress response with genome‐wide association

Abstract: A key component to understanding the evolutionary response to a changing climate is linking underlying genetic variation to phenotypic variation in stress response. Here, we use a genome-wide association approach (GWAS) to understand the genetic architecture of calcification rates under simulated climate stress. We take advantage of the genomic gradient across the blue mussel hybrid zone (Mytilus edulis and Mytilus trossulus) in the Gulf of Maine (GOM) to link genetic variation with variance in calcification r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…As pH tolerance has been shown to exhibit heritability in Mytilus spp. 34,35 , it is possible that multigenerational selection may indeed allow the population to ultimately recover the offset in shell-size observed in this experiment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As pH tolerance has been shown to exhibit heritability in Mytilus spp. 34,35 , it is possible that multigenerational selection may indeed allow the population to ultimately recover the offset in shell-size observed in this experiment.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, we observed elevation of phenotypic variation in the low-pH treatment on days 3 and 7, coinciding with the inferred period of heightened selection (between days 0 and 6). Kingston et al 35 similarly showed that stressful conditions (low pH, high temperature, and low food conditions) released phenotypic variation in calcification rates in two species of Mytilus mussels, and went on to link this variation to a number of loci of moderate effect 35 . While an important avenue of future research is determining which CGV mechanisms (genotype-by-genotype or genotype-by-environment interactions) may be producing such patterns, the economic and ecological importance of marine mussels, as well as their global exposure to declining seawater pH, highlight the need to conserve standing variation in order to allow the adaptive capacity of natural populations to play out as climate change progresses.…”
Section: Discussionmentioning
confidence: 99%
“…The realized heritability to increase survival of M. edulis during a spring mortality outbreak was very high (> 0.55) ( Table 3). Most of the heritabilities estimated in mussel species have been reported for growth parameters (Bai et al, 2017;Brichette et al, 2001;Nguyen et al, 2014;Toro et al, 2004), shell nacre color (Bai et al, 2017), mantle color, toxin accumulation A C C E P T E D M A N U S C R I P T (Pino-Querido et al, 2015), and more recently calcification (Kingston et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As for the samples from the other contact zones, all American samples and two out of five Norwegian samples were from saline habitats, while all the others were from brackish habitats. Salinity conditions in the sampling localities were either taken from the literature [27][28][29][30][31][32] or, in case of the few American and the Barents Sea open coast localities, predicted based on the presence or absence of large rivers nearby.…”
Section: Plos Onementioning
confidence: 99%